DR. AMBEDKAR’S INSIGHT ON LABOUR RIGHTS AND THEIR WELFARE (International Journal of Food and Nutritional Sciences, 2023)
Dr. B.R. Ambedkar is a central figure in Indian history who fashioned the discourse, on labor welfare through his advocacy for social justice, economic rights, and empowerment of marginalized communities. This paper explores Ambedkar's idea of labor welfare and emphasizes his belief in the essential dignity of labor and the need for comprehensive policies that protect workers' rights. Ambedkar argued for the state’s active role in enforcing labor laws, by promoting fair wages, and ensuring safe working conditions for labours. He acknowledged education as a vital tool for empowering workers and advocated for cooperative movements as a means of economic independence. He also criticized capitalist exploitation and gave emphasis on labor organizations for collective bargaining and solidarity among workers. The insights gleaned from Ambedkar’s vision is continued to resonate in contemporary labor policies in the pursuit of equitable labor rights and social justice. This paper aims to provide a comprehensive analysis of Ambedkar’s contributions to labor welfare by highlighting his perspectives within the broader context of socio-economic reform in India.